EFFECTIVENESS OF MENTAL HEALTH TRAINING'S ON COMMUNITY LEADERS' ATTITUDES OF PEOPLE WITH MENTAL DISORDERS: A QUASI EXPERIMENT - Yosua Aldrin Kaligis (Journal of Vocational Nursing, 2026)
Introduction: As a mental health service, community leaders' involvement will aid in the detection and reporting of mental illnesses in the community, assisting in the provision of unambiguous answers to health issues in the community. The significance of leaders in changing the way the community views mental health cannot be overstated. This study aims to ascertain how community leaders' perceptions of people with mental illness evolve following their training and health education. Methods: Using a pre-test and post-test design with a control group, this study was quasi-experimental. Using the Community Attitudes Survey and stratified random sampling, the sample consisted of 84 respondents in total. The Mental Illness Questionnaire. We conduct mental health training daily, followed by a two-week evaluation. Results: According to the study's findings, the intervention group's mean attitude score 24.95, while the control group's was 23.97. Additionally, the intervention group's post-mental health training score was 27.32, while the control group's rating was 25.10. Both the intervention group and the control group had 0.000 (p < 0.05) attitudes, indicating that mental health training had an impact on both groups. With a value of 0.000 (p < 0.05), the difference test results likewise revealed a significant attitude difference. Community leaders develop the capacity to take on a particular mindset. Conclusions: There is an influence on the attitudes of community leaders toward people with mental illness when receiving health education.